EFEKTIVITAS PEMBERIAN VIRGIN COCONUT OIL (VCO) TERHADAP PENCEGAHAN STRIAE GRAVIDARUM PADA KEHAMILAN DI RS PMC: Striae Gravidarum, Virgin Coconut Oil (VCO) - Fenny Fenny; Nia Desriva (STIKes Al-Insyirah Pekanbaru, 2020)
Striae Gravidarum is a common skin disorder that occurs during pregnancy which is commonly found in the mother's stomach. The prevalence of striae gravidarum in pregnant women ranges from 50-90%. The effects of striae gravidarum cause itching, heat and dry and emotional disturbances, causing cosmetic problems in most mothers. Virgin Coconut Oil (VCO) has an effective content to maintain skin elasticity, many contain moderate chain saturated fatty acids, which are believed to be drugs that can prevent striae. This research is a research using analytical survey method with pre experimental design approach with pretest-posttest with control group design. The population in this study was 32 pregnant women who had striae gravidarum, before they were pre-tested by observing the amount of striae, then interventions were carried out by applying Virgin Coconut Oil (VCO) to the belly of pregnant women, after that a posttest was done by re-observing the amount of striae. striae gravidarum. This study uses the Paired Sample T-test hypothesis test to determine the effectiveness of administration of Virgin Coconut Oil (VCO) to prevent straie gravidarum in pregnancy. The application of applying Virgin Coconut Oil (VCO) on the belly of pregnant women carried out for 8 weeks and showed a decrease in the number of straie gravidarum in pregnant women. Based on the effect test using Paired sample T-test in the pre-test group showed the results of p = 0.162 <0.05 and in the post-test group p = 0.000 <0.05. thus it can be concluded the effectiveness of giving Virgin Coconut Oil (VCO) to striae gravidarum in pregnant women.